Does Attitude towards Grammar Affect High-Level Reading Comprehension Skills? - Hatice Güneş (Sakarya University, 2024)
Grammar is a learning area that functionally contributes to effective language skills. The aim of grammar instruction is the acquisition of the four basic language skills based on Turkish language rules. Reading skill, a lingual comprehension skill, aims accurate structuring of the ideas of the author of a text by the reader. The present study aimed to determine the possible effects of the attitudes towards grammar on high-level reading comprehension skills (HLRCS) based on certain variables (gender, final Turkish language course grade, and parental education level). In the current quantitative study, data were collected with the Grammar Attitude Scale and the High-Level Reading Comprehension Test (HLRCT). The study group included 427 8th grade middle school students. In the study, the regression analysis conducted to determine the causality between the Grammar Attitude Scale and HLRCT scores, revealed significant findings. Grammar attitude explained 4% of the variation in the HLRCT scores. Grammar attitude improved the achievements in high-level reading comprehension.